Awareness of Snake bite and its first aid management in rural areas of Maharashtra - Chincholikar, Sanjeev Vasantrao; Bandana, Patniak; Swati, Raje (Indian Journal of Community Health, 2014)
Background: Cause of ‘unacceptable incidence’ of snake bite fatalities is that people try out all kinds of ‘bizarre remedies’ initially. Objectives: To study the knowledge about the types of snakes and their identification and to ascertain the knowledge about first aid. Methods: A cross sectional study was carried out in 10 adopted villages under Rural Health Training Centre, from July 2011 to June 2012. Out of 2272 households, a proportionate sample was selected and one representative from each household was further selected at random. Results: The awareness about first aid measures was less in all subjects but the knowledge about symptoms of snake bite was higher in majority of subjects. It was observed that knowledge about types of snakes was significantly higher in 12-20 years of age group (p <0.05). Out of 49 survived cases of total 68 cases, 8 cases were given wrong first aid. Use of mantriks, sucking of blood was practiced in few cases. In most of the cases the nearest health facility is not in a reachable distance, taking more than 30 minutes to reach and no transport facility is available to reach nearest health centre. Hence, in order to prevent untimely death, there is a need to provide knowledge regarding first aid treatment of snake bite to the villagers.